Adsorption of cadmium (II) ions by polyacrylonitrile-based activated carbon nanofibers/ magnesium oxide as its adsorbents - Che Othman, Faten Ermala (2015)
In this work, activated carbon nanofibers (ACNFs) from precursor polyacrylonitrile (PAN) and magnesium oxide (MgO) were prepared via electrospinning process. The morphological properties of the PAN/MgO based ACNFs were characterized by using Scanning Electron Microscopy (SEM) and the specific surface area were investigated using nitrogen adsorption, Brunauer-Emmett-Teller (BET) methods. Moreover, the functional group analysis was done by using Fourier Transform Infrared (FTIR). Besides that, the sorption study has been conducted in order to determine the adsorption capacity between electrospun ACNFs/MgO, pristine ACNFs and granular activated carbon (GAC) towards cadmium (Cd). The results showed that the specific surface area of modified ACNFs is higher compared to the precursor ACNFs, however the SSA obtained is lower to the theoretical results. SEM micrograph analysis shows more compact nanofibers with aligned nanofibers with average diameter of 200-700 nm. Under batch adsorption study, it was found out that Cd(II) removal of both ACNFs and ACNFs/MgO is higher compared to the commercial GAC. It has been demonstrated that the adsorption capacity of both electrospun ACNFs is higher when compared to the adsorption capacity of commercial GAC towards Cd (II) ions.